Effectiveness of Various Types of Manure and Inorganic Fertilizers on Populations of N-fixing and P-Solubilizing Bacteria and Nutrient Uptake of Maize in Inceptisol - Usman, Alda Inayah A. Hi.; Ustiatik, Reni; Utami, Sri Rahayu; Nuraini, Yulia (The University of Lampung, 2024)
Bacteria are classified as non-symbiotic N-fixing and P-solubilizing play an important role in enhancing soil quality and plant growth. This study aims to analyze various types of manures and inorganic fertilizers on N-fixing and P-solubilizing bacteria population and their relationship with N and P uptake of maize in Inceptisol. The manure used was poultry, goat, and cow manure with doses of 0 t/ha, 10 t/ha, and 20 t/ha, respectively, and inorganic fertilizer NPK Phonska 15-15-15 dose 0 kg/ha; 150 kg/ha (50% of recommendation dose) and 300 kg/ha (100% of recommendation dose). Application of manure (poultry, goat, and cow manure) increased N-fixing and P-solubilizing bacteria population. The application of various types of manure and inorganic fertilizers has a significant impact on N and P uptake. The highest N and P uptake were 29.92 kg/ha and 2.63 kg/ha, respectively. Manure application can reduce inorganic fertilizer dose by up to 50%, increasing plant production efficiency and environmental sustainability. Keywords: Bacteria population, Fertilizer optimization, Inceptisol, Nutrient uptake.